The characterisation of PM 304 stainless steel sintered in the presence of a copper based additive - Uzunsoy, D. (ELSEVIER SCIENCE BV, 2007)
Samples of 304 stainless steel powders alloyed with a range of copper-based additive (2-8 wt.%) have been compacted and sintered at two different temperatures (1250 and 1350 degrees C) an Argon atmosphere. The effect of copper-based ternary alloy on the microstructure and hardness values of a sintered stainless steel has been investigated. It was found that the quantity of copper-based additive as well as the sintering cycle has a profound impact on the microstructure and hardness values of sintered stainless steel. The residual porosity in the sintered specimens was substantially reduced in samples compacted from powder mixtures containing 2-8 wt.% of additives. The microstructural characterisation of PM 304 stainless steel alloyed with different amounts of copper addition shows that copper is homogenously diffused into the base stainless steel. The microhardness values of samples increase with an increase in the amount of additive due to the elimination of porosity. (c) 2006 Elsevier B.V All rights reserved.
Keywords: sintering; powder consolidation; scanning electron microscopy (SEM); stainless steel; hardness; STAINLESS-STEEL; BEHAVIOR; Materials Science; Physics